USING STATED PREFERENCES (SP) TO ANALYZE THE SERVICE QUALITY OF PUBLIC TRANSPORT - Concepcion Roman; Juan Carlos Martin; Raquel Espino (European Regional Science Association (ERSA), 2011)
In order to determine the level of satisfaction of the public transport services, the passengers jointly evaluate the various attributes that represent the different aspects of the level of service. From a methodological viewpoint this means finding the weighting that individuals use to evaluate those attributes within what is considered as the level of global satisfaction or utility. In this paper we obtain indicators that permit the aggregate measurement of the quality of the public transport bus services on Gran Canaria in Spain. The analysis focuses on obtaining the preferences using designs of Stated Preferences (SP) that give the individual the choice between the current service and a hypothetical service defined, from a combination of the most relevant variables. With this information multinomial logit models are estimated that permit us to obtain a linear representation of the utility function parameters, from which a measure of the global quality of the service is obtained. The results of the analysis demonstrate that passengers have clearly different behaviour, depending on whether they are urban or interurban users; this is especially relevant in their perception of certain attributes such as frequency, and to some extent the willingness to pay relative to the components of total travelling time.
Keywords: 330